Planted Forests Greened 7% Slower Than Natural Forests in Southern China Over the Past Forty Years - Zenghui Fan; Jia Sun; Torbern Tagesson; Lunche Wang; Shu Xu; Weifu Tan; Feng Tian; Wentao Ye; Qin Tan; Shaoqiang Wang; Anders Ahlström (Geophysical Research Letters)
Abstract Forests have seen a strong greening trend worldwide, and previous studies have attributed this mainly to land‐use conversions such as afforestation. However, for the greening of existing forests, the role of human interventions is unclear. Here we paired neighboring natural and planted forests in Southern China to minimize the differences between the forest types and analyzed the vegetation index EVI2 from Landsat over 1987 to 2021. The EVI2 trends observed in natural forests can be seen as mainly responses to large‐scale environmental changes, whereas the difference between the forest types represents the impact caused by human interventions. We found that though the mean EVI2 of planted forests was comparable to that of natural forests, the greening trends were overall 7.0% lower in planted forests. Our results suggest that human interventions associated with planted forests did not accelerate their greening, indicating the necessity for refined policies to enhance future forest greening.